Maternal and fetal factors observed with late preterm births - Dey, Madhusudan; Agarwal, Raju; Maji, Devkalyan; Kohli, Uttara A. (International Journal of Research in Medical Sciences, 2017)
Backround: Although neonatal morbidity and mortality rates are fallen in recent decades, the prevalence of preterm deliveries has increased especially late preterm births. Late preterm deliveries are at increased risk of various neonatal complications compared to term deliveries. This study was carried out to identify the maternal characteristics and co-morbidites found with late preterm births and feto-maternal outcome in terms of indication of delivery, route of delivery, Apgar score and NICU admissions. Methods: A retrospective study was conducted in a tertiary care teaching hospital of Indian armed forces between Jan 2011 to Dec 2012 where 248 late preterm deliveries were analysed. Results: 56% women had spontaneous late preterm births and 44% women were induced. 23% of patients had history of 1 or more prior abortion and 13% patients had previous fetal deaths among the patients had late preterm delivery. Common maternal morbidities in mother delivering late preterm were hypertensive disorders of pregnancy (20.6%), anaemia (14.5%) and preterm premature rupture of membrane (13.7%). 4.8% newborns had Apgar ≤ 7 and 10% newborns required NICU admissions. Conclusion: Higher incidences of hypertensive disorders of pregnancy, anaemia and preterm premature rupture of membrane were found with late preterm birth and 10% of newborns required NICU care.